1985
DOI: 10.1149/1.2113881
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Cycling Performance in Improved Lithium Hexafluoroarsenate/2‐Methyl Tetrahydrofuran Electrolytes

Abstract: Lithium hexafluoroarsenate/2-methyl tetrahydrofuran electrolytes have been prepared, purified, and evaluated using half-cell galvanostatic lithium cycling, cyclic voltammetry, plus colorimetric, gas chromatographic, and UV absorption techniques. Superior electrolytes have been prepared yielding reproducible cycling efficiencies in excess of 97%. Static aging trials at ambient temperature clearly demonstrate deterioration in cycling performance with time. This decline in performance is related to electrolyte de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Many organic solvents have been studied for the Coulombic efficiency in Li-metal-anode-based batteries. The cycling efficiency of a Li metal anode was reported to be less than 85% in PC, [104][105][106] 88% in THF, [107][108][109] an average of 96% in 2MeTHF, [109][110][111][112] 97% in polymethoxy ethers 113 and dimethoxy propane, 114 98% in diethyl ether, 109,115 less than 85% in DME or ethyl glyme and less than 50% in diglyme, 116 above 96% in DOL, 52,[117][118][119][120] and about 80% in ILs. [121][122][123][124][125][126] However, Li cells using electrolytes with the aforementioned solvents (except DOL) show poor capacity retention 115,127,128 and internal short circuits due to dendrite growth.…”
Section: Dendrite Prevention By In Situ Formed Stable Sei Lmmentioning
confidence: 99%
“…Many organic solvents have been studied for the Coulombic efficiency in Li-metal-anode-based batteries. The cycling efficiency of a Li metal anode was reported to be less than 85% in PC, [104][105][106] 88% in THF, [107][108][109] an average of 96% in 2MeTHF, [109][110][111][112] 97% in polymethoxy ethers 113 and dimethoxy propane, 114 98% in diethyl ether, 109,115 less than 85% in DME or ethyl glyme and less than 50% in diglyme, 116 above 96% in DOL, 52,[117][118][119][120] and about 80% in ILs. [121][122][123][124][125][126] However, Li cells using electrolytes with the aforementioned solvents (except DOL) show poor capacity retention 115,127,128 and internal short circuits due to dendrite growth.…”
Section: Dendrite Prevention By In Situ Formed Stable Sei Lmmentioning
confidence: 99%
“…Recent advances report that electrolytes used in metallic lithium-based batteries play an important role in adjusting the electrochemical performance such as cyclability, Coulombic efficiency and capacity retention. For instance, in ether-based electrolyte, metallic lithium exhibits much higher Coulombic efficiency than in carbonate-based electrolyte. In situ micro-optical analysis indicates that the lithium dendrite growth could be suppressed in ether-based electrolyte, whereas it is not well alleviated in a carbonate environment. The conducting salts did not always effectively inhibit the dendrite formation because of the volumetric evolution of metallic lithium and the vulnerability of SEI under mechanical deformation upon cycling, although a few functional salts may to some extent. , Nevertheless, the above results still suggested that the choice of solvents/salts, which acted as the second-staged protection against Li dendrite growth, is of great importance once the SEI as the first-staged protection failed.…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, the relationships among charge transfer, mass transfer, and performance of metallic lithium negative electrode in propylene carbonate (PC) and 2-methyl-tetrahydrofuran (2MeTHF) are investigated by microelectrode technique. PC and 2MeTHF are chosen as the electrolytes because they are shown to exhibit obvious discrepancy in charge/discharge cyclic performance. Through this study, we aim to provide clear kinetic mechanism and its possible effects on the performance of secondary lithium batteries, and more importantly, to explore universal electrochemical criteria for the preparation, selection, and optimization of electrolytes toward high battery performance.…”
Section: Introductionmentioning
confidence: 99%
“…1. [25][26][27][28] With the development of LIBs it became clear that LiAsF 6 and LiClO 4 were inappropriate for commercial cells, due to safety and toxicity concerns. Similarly, the relatively low conductivities of electrolytes based on LiTf made also this salt less popular.…”
mentioning
confidence: 99%